Questions and answers on the use of aspirin for primary prevention of cardiovascular disease in diabetes. (September 2022) - Cavallari, Ilaria; Nobile, Edoardo; De Filippis, Aurelio; Veneziano, Francesco; Maddaloni, Ernesto; Ussia, Gian Paolo; Grigioni, Francesco
Abstract: Patients with diabetes have a prothrombotic state and a 2 to 4 times higher risk of cardiovascular events than those without diabetes. Aspirin is the cornerstone of treatment in patients with cardiovascular disease, irrespective of diabetes status, being able to confer a 19% relative risk reduction per year in serious vascular events compared with placebo at long-term follow-up (6.7% vs 8.2% per year, p < 0.0001). Data regarding the benefit-risk ratio of aspirin prescribed to patients with diabetes without established cardiovascular disease are less convincing, especially when compared to other preventive strategies. Of note, in primary prevention trials, aspirin allocation yielded a significant 12% proportional reduction in serious vascular events, irrespective of diabetes status, corresponding to a small annual absolute risk reduction (0.06% per year). However, in everyday clinical practice aspirin is still largely prescribed by both diabetologists and cardiologists. In this article, we provide eight questions and answers corroborated by available evidence on the use of aspirin for primary prevention of cardiovascular disease in diabetes.